2018
DOI: 10.1002/joc.5393
|View full text |Cite
|
Sign up to set email alerts
|

Estimating uncertainty associated with the standardized precipitation index

Abstract: We investigate methodological uncertainties associated with the standardized precipitation index (SPI) that result from limited record length, trends, and outliers. We use long, homogenous records from 14 Italian stations to investigate how specific features in the precipitation record affect construction of an underlying gamma probability function. We apply a resampling scheme to the long records in order to estimate confidence intervals associated with a range of precipitation characteristics. Stability in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
(45 reference statements)
2
16
0
Order By: Relevance
“…In addition, the minimum length of record also depends on whether the precipitation pattern changes (Wu et al, 2005). Carbone et al (2018) found that extreme events also have a significant influence on SPI estimates, even over 60-years of records.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the minimum length of record also depends on whether the precipitation pattern changes (Wu et al, 2005). Carbone et al (2018) found that extreme events also have a significant influence on SPI estimates, even over 60-years of records.…”
Section: Discussionmentioning
confidence: 99%
“…McKee et al (1993) regarded that a continuous period of at least 30-years seems ideal in the SPI calculation, while Guttman (1994) found that ∼40 to 60-years of record is needed for parameter estimation stability in the central part of the distribution and ∼70 to 80-years of record for stability in the tails. Carbone et al (2018) suggested that record lengths of 60-years are basically enough in general, which typically results in stable parameters and representative SPI values. In addition, the minimum length of record also depends on whether the precipitation pattern changes (Wu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations